Environmental Performance Analysis Using the Green Productivity Method on Convection Waste Baper Shop Surabaya - Muhammad Syafiqul Hamizan; Wiwik Handayani (International Journal of Business and Applied Economics, 2023)
The aim of this research is to analyze the environmental performance of solid waste and liquid waste using the Green Productivity (GP) method. Konveksi Baper Shop is a micro business that operates in the field of making women's clothes. This research method uses a quantitative descriptive approach aimed at providing suggestions for improvements to increase company productivity. The results of the research showed that the company had an initial Environmental Performance Index (EPI) of 23,076. Meanwhile, the initial Green Productivity Index (GPI) at the Baper Shop convection had a value of 0.076 and solid waste GP was 0, 048 and liquid waste GP of 1.01. There are 2 There are two alternative solutions planned with the first alternative in the form of using liquid waste to become liquid organic fertilizer and the second alternative in the form of using solid waste to make patchwork mats. It can be concluded that by improving environmental performance in the form of using liquid and solid waste it can increase the company's income.